2006
DOI: 10.1007/s00113-005-1037-6
|View full text |Cite
|
Sign up to set email alerts
|

Perkutane dorsale versus offene Instrumentation bei Frakturen des thorakolumbalen Übergangs

Abstract: The open procedure caused permanent and significant damage to the strongest extensors of the autochthonus back musculature, the m. multifidus, which results from multisegment combined damage to the r. posterior nervi spinalis and muscle fibres. In contrast, percutaneous placement of an internal fixative reduces perioperative access morbidity causing little iatrogenic damage to back muscles and only a minor perioperative blood loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(34 citation statements)
references
References 19 publications
0
22
0
4
Order By: Relevance
“…However Grass et al [11] found no significant difference in operation time, radiation time and accuracy of screw placement. In our own clinical experience and in the present study we found indeed longer radiation times within the percutaneous group.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…However Grass et al [11] found no significant difference in operation time, radiation time and accuracy of screw placement. In our own clinical experience and in the present study we found indeed longer radiation times within the percutaneous group.…”
Section: Discussionmentioning
confidence: 94%
“…Herewith tissue dissection, blood loss and hospitalisation should be reduced. This raises hope that the treatment of patients can be improved and some promising results have been published [8,11,21,26]. A derivative design of the percutaneously inserted spinal fixation systems that are available has already improved the surgical technique.…”
Section: Introductionmentioning
confidence: 99%
“…Using this technique, significant reduction of blood loss was achieved. Grass et al [8] showed an average blood loss of 43 ml (10-90 ml) versus the open approach needing 870 ml (570-1,200 ml). A faster rehabilitation due to the less invasive technique has been described by different current publications [3,5,6,22].…”
Section: Introductionmentioning
confidence: 99%
“…Although percutaneous posterior instrumentation has been described in several clinical studies [1,4,11,13,15,17,18,23,24], there is lack of data in the literature concerning their use in thoracic and lumbar spine fractures. Traditional open thoracolumbar instrumentation results in significant iatrogenic damage of the vital dorsal musculoligamentous complex [8,10,19,21].…”
Section: Introductionmentioning
confidence: 99%
“…1,2) PPSs are usually inserted using a mobile fluoroscope, such as a C-arm. Recently, surgical support devices used when inserting pedicle screws have been undergoing rapid development, and performing more accurate and minimally invasive surgery has become possible by (i) combining a navigation system with a mobile fluoroscope that can acquire three-dimensional images, such as the Arcadis Orbic Isocentric C-arm (Siemens Healthcare, Germany) 3,4) or the O-arm (Medronic, USA), 57) or (ii) combining a navigation system with a Computed tomography (CT) device 8,9) or the mobile CT device Airo (Brainlab AG, Germany).…”
Section: Introductionmentioning
confidence: 99%